A meta-analytic investigation of the role of reward on inhibitory control. Issue 10 (October 2021) - Burton, Sam; Knibb, Graeme; Jones, Andrew
Contemporary theories predict that inhibitory control (IC) can be improved when rewards are available for successfully inhibiting. In non-clinical samples empirical research has demonstrated some support; however, "null" findings have also been published. The aim of this meta-analysis was to clarify the magnitude of the effect of reward on IC and identify potential moderators. A total of 73 articles (contributing k = 80 studies) were identified from PubMed, PsycInfo, and Scopus, published between 1997 and 2020, using a systematic search strategy. A random effects meta-analysis was performed on effect sizes generated from IC tasks, which included rewarded and non-rewarded inhibition trials. Moderator analyses were conducted on clinical samples (vs "healthy controls"), task type (go/no-go vs stop signal vs Flanker vs Simon vs Stroop vs Anti-saccade), reward type (monetary vs points vs other), and age (adults vs children). The prospect of reward for successful inhibition significantly improved IC (SMD = 0.429, 95% CI = 0.288, 0.570, I 2 = 96.7%) compared with no reward conditions/groups. This finding was robust against influential cases and outliers. The significant effect was present across all IC tasks. There was no evidence of the effect moderated by type of reward, age, or clinical samples. Moderator analyses did not resolve the considerable heterogeneity. The findings suggest that IC is a transient state that fluctuates in response to motivations driven by reward. Future research might examine the potential of improving IC through rewards as a behavioural intervention.